Lactate Induces the Expressions of MCT1 and HCAR1 to Promote Tumor Growth and Progression in Glioblastoma - Longhitano, Lucia; Vicario, Nunzio; Tibullo, Daniele; Giallongo, Cesarina; Broggi, Giuseppe; Caltabiano, Rosario; Barbagallo, Giuseppe Maria Vincenzo; Altieri, Roberto; Baghini, Marta; Di Rosa, Michelino; Parenti, Rosalba; Giordano, Antonio; et al. (Frontiers in Oncology, 2022)
Tumor microenvironment (TME) plays a pivotal role in establishing malignancy and it is associated with high glycolytic metabolism and increased lactate production accumulating in TME through monocarboxylate transporters (MCTs). Several lines of evidence suggest that lactate also serves as a signalling molecule through its receptor Hydroxycarboxylic acid receptor 1 (HCAR1) thus functioning as a paracrine and autocrine signalling molecule in TME. The aim of the present study was to investigate the role of lactate in glioblastoma (GBM) progression and metabolic reprogramming in an in vitro and in vivo model. Cell proliferation, migration and clonogenicity assay were performed in vitro on three different human GBM cell lines. Protein expression of MCT1, MCT4 and pharmacological lactate receptor (GPR81) were evaluated both in vitro and in a zebrafish GBM in vivo model. These results were further validated in patient-derived GBM biopsies. Our results showed that lactate significantly increased cell proliferation, migration and colony formation capacity of GBM cells, both in vitro and in vivo. We also showed that lactate increased MCT1 and HCAR1 expression. Moreover, lactate modulated epithelial-mesenchymal transition protein markers E-Cadherin and β-Catenin. Interestingly, lactate induced mitochondrial mass and OXPHOS gene suggesting an improved mitochondrial fitness. Similar effects were observed after treatment with 3,5-Dihydroxybenzoic acid, a known agonist of GPR81. Consistently, GBM zebrafish model exhibited an altered metabolism and increased expression of MCT1 and HCAR1 leading to high levels of extracellular lactate and thus supporting tumor cell proliferation. Our data from human GBM biopsies also showed that in high proliferative GBM biopsies, Ki67 positive cells expressed significantly higher levels of MCT1 compared to low proliferative GBM cells. In conclusions our data suggest that lactate favours proliferation of neighbourhood cells by cooperating with their glycolytic metabolism, sensing and removing extracellular lactate. In particular, lactate and its transporter and receptor play a major role in GBM proliferation and migration thus representing a potential target to develop new strategies to counteract tumor progression and recurrencies.